Czy strach przed przemocą może stanowić realną podstawę porządku politycznego? Rozmyślania śladami T. Hobbesa - Szklarska, Anna (Dialogi Polityczne, 2018)
In the article, inspired by philosophy of politics of Thomas Hobbes, the author discusses the issue of the foundations of social order and the meaning of violence legitimized by state apparatus which is used to stabilize and protect the state. Human, according to Hobbes, by seeking shelter from chaos and violence falls into embrace of authority which constitutes a type of violence sanctioned by means of law. But is another perspective possible?